A new plethodontid salamander (Bolitoglossa sooyorum) from Costa Rica - Vial, James L. (1963)
A new species of plethodontid salamander, Bolitoglossa sooyorum, is described from the Tropical Montane Wet Forest of the Cerro de la Muerte of Costa Rica. It is distinguished from other species on the basis of its slender body form, markings and elongate limbs. It is closely related to B. marmorea of Panamá.